PEMBINAAN KARAKTER MANDIRI ANAK ASUH (Studi Realitas Pembinaan Karakter Mandiri Anak Asuh di Panti Asuhan Putri Muhammadiyah Kecamatan Pekuncen Kabupaten Banyumas) - Ikhwani, Ikhwani (Jurnal Tawadhu, 2020)
This research has several backgrounds. First, the self reliance is one of the formulations in the goals of national education. Second, the self reliance is a national character that must be built. Third, crisis of self reliance appears in society. Fourth, not all children / adolescents receive adequate care, including fostering self reliance from the family environment. Fifth, orphanages have a significant influence in handling children / adolescents who experience neglect problems. The formulation of the problem posed is how the concept of self reliance developed by the orphanage, how is the self reliance character development process applied to foster children in orphanages, how is the impact of this self reliance character development for orphaned children in orphanages. The approach used is phenomenology approach with analytical descriptive methods. The research was focused on Panti Asuhan Putri Muhammadiyah Kecamatan Pekuncen Kabupaten Banyumas. The data collected using observation techniques and in-depth interviews with the object of research. The research produces several conclusions. First, the foster children showed a good level of self reliance. Second, the efforts of the orphanage in creating the self reliance of foster children. Third, the supporting factors. Fourth, the inhibiting factors. Fifth, the model for developing self-reliance on the orphanages